Relationship in Between FDI Inflow and Economic Growth in Kosovo - Islami, Xhavit; Mulolli, Enis; Skenderi, Nagip (European Journal of Economics and Business Studies, 2016)
This study treats the relationship of foreign direct investment (FDI) and economic development in Kosovo. FDI is considered as an important factor of economic growth of places in development, so rightly the question is asked: “Which is the impact of FDI inflow on economic growth of Kosovo?” This study shows the relationship in between FDI inflow and five macroeconomic indicators that have an important role in economic development of Kosovo such as: GDP, GDP per capita, GNI, Exports, and Balance Trade. The data were taken from World Bank and the statistic agency of Kosovo for 2005 to 2014 period. Pearson Correlation technique was used for empirical analysis that is realized with SPSS v. 21.0 statistical program, the results showed that there is a positive relationship in between FDI inflow and GDP growth, whereas there is a negative relationship of FDI inflow and trade balance of Kosovo. This study arguments what is necessary to be done in leading policies to attract foreign direct investment in Kosovo.
Keywords: FDI inflow, GDP, economic growth, GNI, Balance trade, Kosovo.